The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Oxford Scholarship Online 2018
DOI: 10.1093/oso/9780198794844.003.0017
|View full text |Cite
|
Sign up to set email alerts
|

Developing actionable biometric insights for production teams

Abstract: In this chapter we describe the challenges and learnings in establishing processes for developing actionable biometric procedures for production teams. The chapter, divided in four main sections, describes the ongoing efforts of recent years to facilitate the incorporation of the science of biometrics into the culture of video game production, as illustrated through several case studies. The end goal is making biometric data an accessible option in the tool chest of user researchers and an ally in the team’s d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…While fMRI and EEG are more likely, in the future, to pinpoint specific brain-related activity patterns or areas directly involved (or highly correlated) with the sense of presence (as in the somewhat related field of awareness; see Koivisto et al, , 2017Jimenez et al, 2018), SC and HR are more likely to identify secondary effects of presence, as well as experiences modulated by or together with presence, such as, for example, arousal, emotion, and stress (Poels et al, 2012;Chalfoun and Dankoff, 2018). Furthermore, there are myriad data collection and data analysis modalities for SC (SCR, SCL, and GSR peak amplitude/number, just to cite a few), and this makes the comparison of the various methodologies that employ SC almost impossible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While fMRI and EEG are more likely, in the future, to pinpoint specific brain-related activity patterns or areas directly involved (or highly correlated) with the sense of presence (as in the somewhat related field of awareness; see Koivisto et al, , 2017Jimenez et al, 2018), SC and HR are more likely to identify secondary effects of presence, as well as experiences modulated by or together with presence, such as, for example, arousal, emotion, and stress (Poels et al, 2012;Chalfoun and Dankoff, 2018). Furthermore, there are myriad data collection and data analysis modalities for SC (SCR, SCL, and GSR peak amplitude/number, just to cite a few), and this makes the comparison of the various methodologies that employ SC almost impossible.…”
Section: Discussionmentioning
confidence: 99%
“…In the present article, the abbreviation "SC" will be used to refer to this methodology. The use of SC is well-documented in the literature on human emotion and cognition (Weber et al, 2009;Poels et al, 2012;Chalfoun and Dankoff, 2018). SC is associated, for example, with stress, excitement, engagement, and frustration, and arousal, among other factors (see e.g., Kurniawan et al, 2013).…”
Section: Use Of Physiological Measuresmentioning
confidence: 99%
“…However, multiitem questionnaires may be time consuming to administer, and therefore, completing the questionnaire during a VR experience could significantly disrupt the sense of presence experienced by the user. Several studies have examined continuous physiological indices of sense of presence (for a recent study, see [35]); however, these have several drawbacks, such as being highly modulated by confounding or secondary effects of presence such as arousal, stress, or emotion [36]. The current experiment employs short, single-item measurements administered orally by the experimenter during the VR session.…”
Section: Related Work and Study Objectivesmentioning
confidence: 99%
“…The current experiment employs short, single-item measurements administered orally by the experimenter during the VR session. Short measurements have been used in research on sense of presence (see the Brief Measure of Presence) [36] and CS (see the Fast Motion Sickness Questionnaire) [37,38]. Research has shown single items to be valid and reliable, even if they do not address all the aspects of the psychological constructs that it aims to measure [34,39].…”
Section: Related Work and Study Objectivesmentioning
confidence: 99%
“…In the present article, the abbreviation "SC" will be used to refer to this methodology. The use of SC is well-documented in the literature on human emotion and cognition (Weber et al, 2009;Poels et al, 2012;Chalfoun and Dankoff, 2018). SC is associated, for example, with stress, excitement, engagement, and frustration, and arousal, among other factors (see e.g., Kurniawan et al, 2013).…”
Section: Use Of Physiological Measuresmentioning
confidence: 99%